Sifat Anatomi dan Kualitas Serat Kayu Afrika sebagai Bahan Baku Pulp dan Kertas: Anatomical Properties and Quality of African Wood Fiber as A Raw Material for Pulp and Paper - Lestari, Dini; Ningsih, Rima Vera; Fahrussiam, Fauzan (Forestry Faculty of Hasanuddin University, 2023)
Nowdays, there is growing interested in development of afrika wood utilization. Afrika wood is one fast growing species from plantation forest. The objective of this research was to evaluated of characterization of afrika fiber for pulp and paper production. Anatomical properties of afrika wood were also investigated. Determination of characterization of fiber dimension was conducted based on Tappi (1989). The resulted showed that afrika wood have type of porous namely soliter and radial multiple porous. The parenchyma and ray characters were paratracheal parenchyma confluent and multiseriate types. For fiber characteristic obtained by fiber length, fiber diameter, lumen diameter, and cell wall thickness were 935.33 µm, 28.52 µm, 21.29 µm, and 3.62 µm respectively. The derived value of afrika fibers obtained by runkel ratio, felting power, muhlsteph ratio, coefficient of rigidity, flexibility ratio, and fiber length were 0.43, 35.02, 20.51, 0.12, 0.76, and 935.33 µm respectively. Based on the derived value of afrika fibers, it qualifies as Grade II material for pulp and paper production. Afrika wood can be used as raw material for pulp and paper production.